Diseño y construcción económica de sensores, un aporte a la industria y a la academia - Rairán Antolines, Danilo; Olarte Novoa, Yovanny; Peñuela Méndez, César (Ingeniería, 2008)
In this paper we present the construction process of four analog sensors used in converting level, position, and temperature to voltage. Each device serves two primary purposes: first, to promote the magnetic levitation research group's goals, and secondly, to offer the Colombian industrial community alternatives for economical implementation of process monitoring devices. In the article's conclusion, as an important result of the experience acquired designing and building these devices a methodology is proposed for developing these or similar devices as needed by the academic or industrial community.